Usaha Politik Hindia Belanda Terhadap Arus Perlawanan Umat Islam (Studi Jabatan Mufti di Hulu Sungai) - Alfianoor Alfianoor; Nuril Khasyiin (Pascasarjana UIN ANTASARI Banjarmasin, 2022)
This paper discusses the political movement of the Dutch East Indies in Hulu Sungai by looking at the position of the mufti as an important position used by the Dutch East Indies government against the resistance of Muslim movements. Although the Dutch East Indies government at that time was considered the owner of the rightful government. However, the resistance movements against this government continued to the roots of the lower classes of society. This paper aims to find out what the Dutch East Indies political efforts and steps were in resisting the massive movements of the Hulu Sungai community. Mufti became the center issue to create government stability. This study uses historical research methods by looking at historical data as a source of information. In this study it was found, that the Dutch East Indies used two forms of political resistance against Muslim movements, namely; soft political power and hard political power. Hard political power can be seen from the forcible arrest of parties who are considered rebellious. Meanwhile, soft political power is formed by forming and appointing the mufti to become a mediator and stabilizer in the community.